Institutional Dualism in Social Forestry: Village Authority Implementation in Pesanggrahan - Alfian Difa Nagara; Maya Puspita Dewi (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
Indonesia's Social Forestry program provides conditional access to community-based management of state forests under state oversight and regulatory conditions. One of its key schemes, Hutan Desa designates village governments as formal managers through Village Forest Management Institutions (LPHD). This study examines implementation in Pesanggrahan Village, Batu City, where LPHD Mayangsari coexists with the long-established Forest Village Community Institution (LMDH). Prior Hutan Desa studies (Rakatama & Pandit, 2020; Sahide et al., 2020) have predominantly examined rural-district contexts. This research addresses this gap by examining implementation in an urban-administrative municipality structurally lacking a dedicated municipal forestry office‒an underexplored administrative context for social forestry policy. A descriptive qualitative approach with a single intrinsic case study design was employed. Data were gathered through in-depth interviews with purposively selected informants, field observations at the Tumpak Seruk Forest, and systematic document analysis. The analytical process operationalized content, discourse, and narrative analysis to decode actor strategies, rhetorical framing, and historical power configurations. Findings reveal that LPHD's formal legal recognition did not secure operational control in practice. LMDH retained stronger farmer loyalty due to decades-long patronage and clearer benefit-sharing. The Village Head responded by orchestrating joint activities—such as the November 2025 tree planting event that allowed both institutions to remain operationally visible rather than pursuing direct institutional confrontation. These findings suggest that implementation of village authority in social forestry is shaped not only by legal design, but also by institutional history, resource constraints, and the discretionary strategies of local actors.